(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
This essay is an effort to make visible the evolution on Latin Americans thoughts, recovering methodical contributions made by Ricardo Falla, during the investigation process that he made on the massacre that was perpetrated in the Chuj community of San Francisco de Nentón, Guatemala, in 1982. His strategy is based on the Active Participatory Research (Investigación Acción Participativa), focusing on validating the testimony of three indigenous survivors. The legal aspects acquire special relevance as the witnesses must be who they say they are, otherwise, it is not possible to demand justice. The body of the crime must appear as in its absence the crime doesnt exist. This work constitutes a literary contribution, giving voice to the absent voices through a connotation of art. The testimony is to bring life to the story that was not told, San Francisco de Nentón did not die, his social fabric was dispersed and hurt, the need to do justice to the indigenous communities od Guatemala and America is urgent. Ricardo Falla assures us that its possible to research from the oppressed point of view.